Penerapan Algoritma Dijkstra dalam Pencarian Rute Terpendek Wisata Religi - Santoso, Kiswara Agung; Afifah, Zakiyatul; Halikin, Ikhsanul (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2023)
Pilgrimages to the graves of Waliyullah and the spreaders of Islam have become spiritual or religious tourism for Muslims in Java and even almost all Muslims in Indonesia. This opens up opportunities for travel agents to help pilgrims on religious tourism trips. One travel agency that offers religious tour packages is PT Mitra Jaya Group which operates in the Banyuwangi area, East Java. Many travel agencies are trying to increase their competitiveness, to survive competition between travel agencies, especially in improving services and financial management. One way that can be done is to determine the shortest route for religious tourism so that the distance traveled is minimal, where previously the route chosen was not based on proper research. In this paper, the search for the shortest route is carried out by applying the Dijkstra algorithm. The application of the Dijkstra algorithm can provide benefits regarding the shortest distance to religious tourism routes from PT Mitra Jaya Group. From the analysis results, the total shortest distance obtained was 2768.8 kilometers. The resulting shortest route distance is smaller than the distance before using the Dijkstra algorithm, namely 3005.6 kilometers. The difference is 236.8 kilometers and there is a distance saving of 7.87